Criminality, public security and sustainability in tourist destinations: exploratory essay about the Brazilian academic production (2004-2018) - Enrique Costa, Jean (2019)
This study aims to: a) raise papers carried out in the Brazilian reality about the tourist problematic, public security and criminality; b) perform a critical reading of each paper; c) weave a diagnostic of its state of the art, seeking to point the suggested ways, some gaps perceived and the possibilities of connections between the researches. In terms of methodology, it is a bibliographic research of theoretical analysis. It does not attach to methodological conventions of a biometrical research, neither it carries out a quantitative content analysis with the textual material raised. It is a free essayistic exercise. The temporal cut was established in the most dilated possible, being from the year of publication of the first paper found until the last one (2004-2018). The papers were collected in free form in Scholar Google and the CAPES Periodical Portal. As conclusions, it was verified that a significant part of Brazilian studies does not reproduce the media alarm regarding to the social fear as a determinant factor to the distance of tourists. However, we problematize that part of these studies, or almost all of them, does not relate the increasing of criminality (and its multiple possibilities of manifestation) to the variations of tourist demand in dilated temporal series, neither “spatializes” the criminality by zones/areas, viewing to correlate the meetings – and divergences – to the tourist dynamics. Furthermore, we reinforce that part of the researches also does not conduct the effort of typifying the main crimes against the tourist (highlighting the damage, time and place) and in which way this violence can affect the sustainability of the tourist spaces and the image of the places. In this way, some researches repeat clichés already learned in the tourism field that the systemic crime and violence distance tourism, or, ideally, crimes are, in their majority, against property (thefts and robberies).